Integration and Regression of Implanted Engineered Human Vascular Networks During Deep Wound Healing. (13th March 2013) - Hanjaya-Putra, Donny; Shen, Yu-I; Wilson, Abigail; Fox-Talbot, Karen; Khetan, Sudhir; Burdick, Jason A.; Steenbergen, Charles; Gerecht, Sharon
Abstract : This study assessed the functionality and durability of engineered human vasculatures from endothelial progenitors when implanted in a mouse deep burn‐wound model. Human vascular networks, derived from endothelial colony‐forming cells in hyaluronic acid hydrogels, were transplanted into third‐degree burns. Collectively, the findings suggest that human vasculature engineered from endothelial colony‐forming cells can integrate with the host vessels in a deep third‐degree burn model and that hyaluronic acid hydrogels that support the precise formation of human vasculature in vitro can be successfully delivered to the site of injury, where they can survive and integrate with the host vasculature. Abstract : The ability of vascularized constructs to integrate with tissues may depend on the kinetics and stability of vascular structure development. This study assessed the functionality and durability of engineered human vasculatures from endothelial progenitors when implanted in a mouse deep burn‐wound model. Human vascular networks, derived from endothelial colony‐forming cells in hyaluronic acid hydrogels, were transplanted into third‐degree burns. On day 3 following transplantation, macrophages rapidly degraded the hydrogel during a period of inflammation; through the transitions from inflammation to proliferation (days 5–7), the host's vasculatures infiltrated the construct, connecting with the human vessels within the wound area. The growth of mouse vessels near the wound area supported further integration with the implanted human vasculatures. During this period, the majority of the vessels (∼60%) in the treated wound area were human. Although no increase in the density of human vessels was detected during the proliferative phase, they temporarily increased in size. This growth peaked at day 7, the middle of the proliferation stage, and then decreased by the end of the proliferation stage. As the wound reached the remodeling period during the second week after transplantation, the vasculatures including the transplanted human vessels generally regressed, and few microvessels, wrapped by mouse smooth muscle cells and with a vessel area less than 200 μm 2 (including the human ones), remained in the healed wound. Overall, this study offers useful insights for the development of vascularization strategies for wound healing and ischemic conditions, for tissue‐engineered constructs, and for tissue regeneration.